ПСИХОКОРЕКЦІЯ ПРОЯВІВ СОЦІАЛЬНО-ПСИХОЛОГІЧНОЇ ДЕЗАДАПТАЦІЇ УЧАСНИКІВ БОЙОВИХ ДІЙ - Кочубинська, Тамара (My University, 2021)
Мета дослідження – теоретичне конструювання та апробація авторської методики психокорекції проявів соціально-психологічної дезадаптації учасників операції Об’єднаних сил. Методи. Для досягнення мети дослідження були застосовані такі методи дослідження: теоретичні: філософсько-психологічний аналіз дослідження, узагальнення теоретико-методологічних підходів, моделювання та конструювання; емпіричні: формувальний експеримент з використанням психодіагностичного комплексу методик; методи математичної обробки даних: порівняльний аналіз за t-критерієм Стьюдента. Реалізація програми психокорекції відбувалася відповідно до 5 етапів: діагностичного, інформаційно-просвітницького, індивідуальної психокорекції, групової психокорекції, оцінки ефективності. Участь у запропонованій програмі психокорекції взяли 38 учасників ООС. Для встановлення достовірності психокорекційної програми, а саме виключення вірогідності вікових динамічних змін, експериментальне дослідження проводилося з 40 учасниками ООС, які не брали участь у програмі психокорекції. Результати. В запропонованій програмі представлені засоби психокорекційного впливу: виокремлено просвітницький блок (лекції, навчальні семінари, програми соціально-психологічного супроводу) та блок психокорекційної роботи (індивідуальна та групова психокорекція), що впливали на прояви соціально-психологічної дезадаптації учасників ООС та сприяли виникненню конструктивних особистісних змін. Основним завданням програми психокорекції є особистісні зміни учасників ООС: гармонізація Я-концепції; емоційна складова: підвищення рівня прояву емоційного комфорту, зниження рівня прояву негативних емоцій: тривожності, агресивності, депресивності; комунікативна складова: підвищення комунікативного потенціалу та конструктивних способів взаємодії; поведінкова складова: вироблення конструктивних поведінкових стратегій; мотиваційно-ціннісна складова: гармонізація екстернальності та інтернальності, підвищення мотивації долання перешкод, конструктивні ціннісні орієнтації. За результатами порівняльного дослідження за t-критерієм Стьюдента для залежних вибірок встановлені якісні відмінності в показниках соціально-психологічної дезадаптації учасників ООС до та після участі у психокорекційній програмі: знизилися прояви показників по шкалах Я-фізичне і Я-сімейне; знизилися прояви агресивності, зокрема переживання образи, фізичної; особистісної тривожності; дезадаптації; неприйняття себе; емоційний дискомфорт; внутрішній контроль. Висновки. Результати формувального дослідження підтверджують ефективність пропонованої програми психокорекції.

Purpose. The purpose of the study is theoretical construction and approbation of the author's method of psychocorrection of manifestations of socio-psychological disadaptation of the participants of the Joint Forces operation (JFO). Methods. The following research methods were applied to achieve the aim of the study: theoretical: philosophical and psychological analysis of the study, generalization of theoretical and methodological approaches, modelling and construction; empirical: forming experiment using the psychodiagnostic complex of techniques; methods of mathematical data processing: comparative analysis using Student's t-test. The implementation of the psycho-correctional program took place according to 5 stages: diagnostic, informational and educational, individual psychocorrection, group psychocorrection, and evaluation of effectiveness. Thirty-eight participants of JFO took part in the proposed psycho-correctional program. The experimental research was conducted with 40 combatants of JFO who did not participate in the psycho-correctional program to establish the reliability of the psycho-correctional program, namely to exclude the probability of age-related dynamic changes. Results. The proposed program represents the means of psycho-correctional effect: the educational block (lectures, training seminars, programs of social and psychological support) and the block of psycho-correctional work (individual and group psychocorrection) are singled out, that influenced the manifestations of social and psychological disadaptation of participants of JFO and contributed to the emergence of constructive personal changes. The main task of the psycho-correctional program is personal changes of JFO participants, harmonization of Self-concept in particular. Emotional constituent comprises increasing the level of manifestation of emotional comfort and reducing the level of manifestation of negative emotions (anxiety, aggression, depression). Сommunicative constituent includes increasing the communicative potential and constructive ways of interaction. Behavioural constituent embodies the development of constructive behavioural strategies, motivational and value constituent comprises harmonization of externality and internality, increasing motivation to overcome barriers, and constructive value orientations. According to the results of the comparative analysis using Student's t-test for dependent samples, the qualitative differences in the indicators of socio-psychological disadaptation of JFO combatants before and after participation in the psychocorrection program were determined. The manifestations of indicators on the Physical Self and Familial Self scales have decreased. Manifestations of aggression, in particular feelings of resentment, physical and personality anxiety, disadaptation, self-rejection, emotional discomfort, internal control have reduced. Conclusions. The results of the forming research experiment confirm the effectiveness of the proposed program of psychocorrection.
Psychocorrection of manifestations of socio-psychological disadaptation of combatants
Keywords: психокорекція; соціально-психологічна дезадаптація; учасники операції об’єднаних сил; принципи психокорекції; засоби психокорекції; особистісні зміни; 159.99